2008
DOI: 10.1007/s00018-008-7578-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of phagocytic uptake in mammalian cells

Abstract: Phagocytosis is a highly conserved, complex process that has evolved to counter the constant threat posed by pathogens, effete cells and debris. Classically defined as a mechanism for internalising and destroying particles greater than 0.5 mum in size, it is a receptor-mediated, actin-driven process. The best-studied phagocytic receptors are the opsono-receptors, FcgammaR and CR3. Phagocytic uptake involves actin dynamics including polymerisation, bundling, contraction, severing and depolymerisation of actin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
204
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(212 citation statements)
references
References 181 publications
(228 reference statements)
4
204
0
4
Order By: Relevance
“…14 It involves sequential instigation of receptors as a result of cell surface recognition of cargo, leading to internalizations by encircling it into triggered cup-shaped cell membrane deformations, forming a phagosome. 9 The pathway begins with opsonization of the NPs, which then attach to the cell surface via Fc receptors and complement receptors, 15 marking the beginning of actin polymerization and rearrangement and membrane extension to form surface extensions that encapsulate the opsonized NPs for internalization ( Figure 4). 14,16 A reduction and contraction of actin at the base of the cup allows for closure of the phagosome and the entire actinlined phagosome is then internalized with its contents.…”
Section: Phagocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…14 It involves sequential instigation of receptors as a result of cell surface recognition of cargo, leading to internalizations by encircling it into triggered cup-shaped cell membrane deformations, forming a phagosome. 9 The pathway begins with opsonization of the NPs, which then attach to the cell surface via Fc receptors and complement receptors, 15 marking the beginning of actin polymerization and rearrangement and membrane extension to form surface extensions that encapsulate the opsonized NPs for internalization ( Figure 4). 14,16 A reduction and contraction of actin at the base of the cup allows for closure of the phagosome and the entire actinlined phagosome is then internalized with its contents.…”
Section: Phagocytosismentioning
confidence: 99%
“…14,16 A reduction and contraction of actin at the base of the cup allows for closure of the phagosome and the entire actinlined phagosome is then internalized with its contents. 15 In a macropinocytotic manner, the vesicle undergoes degradation after transporting the opsonized particle into the cell.…”
Section: Phagocytosismentioning
confidence: 99%
“…Disassembly of actin filaments has been linked to myosin filament assembly (32), contraction, and changes in cell shape, all of which are needed for efficient phagocytosis. Myosin superfamily motor proteins interact with actin filaments to generate contractile forces that are critical for phagosome development (33). Myosin molecules are hexamers composed of myosin heavy chain dimers and two pairs of myosin light chains (34).…”
mentioning
confidence: 99%
“…118 The conventional particle size for phagocytosis starts at around 0.5 µm. 119 However, some studies have shown that the optimal size range of drug carriers is between 200 nm and 3 µm. …”
Section: Cellular Uptakementioning
confidence: 99%